2013
DOI: 10.1103/physrevlett.111.186101
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Assembly of Magic NumberC60-Au Complexes

Abstract: We report the assembly of magic number (C60)m-(Au)n complexes on the Au(111) surface. These complexes have a unique structure consisting of a single atomic layer Au island wrapped by a self-selected number (seven, ten, or twelve) of C(60) molecules. The smallest structure consisting of 7 C60 molecules and 19 Au atoms, stable up to 400 K, has a preferred orientation on the surface. We propose a globalized metal-organic coordination mechanism for the stability of the (C(60))(m)-(Au)n complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(75 citation statements)
references
References 39 publications
9
66
0
Order By: Relevance
“…The origin of such molecules is not yet clear, but one proposal was that the superbright molecules are pushed up by Ag adatoms [41]. Given the high mobility of Au surface atoms, and the propensity of C 60 molecules to climb onto Au(111) islands [24], it seems plausible that such a mechanism could occur on Au(111), but we have not observed any such molecules in the equilibrium monolayer, nor have any been reported.…”
Section: Discussionmentioning
confidence: 76%
“…The origin of such molecules is not yet clear, but one proposal was that the superbright molecules are pushed up by Ag adatoms [41]. Given the high mobility of Au surface atoms, and the propensity of C 60 molecules to climb onto Au(111) islands [24], it seems plausible that such a mechanism could occur on Au(111), but we have not observed any such molecules in the equilibrium monolayer, nor have any been reported.…”
Section: Discussionmentioning
confidence: 76%
“…Among the different systems under scrutiny, unusual and complex features have been reported for fullerene adsorption on Au(111) and Ag(111) surfaces [12][13][14][15][16][17][18][19][20]. Recently, Xie et al have reported the formation of magic number C 60 -Au complexes stabilized by a globalized metal-organic coordination mechanism [21]. It is thought that such process could inspire further studies aiming to design arrays of magnetic quantum dot for spin applications.…”
Section: Introductionmentioning
confidence: 99%
“…The magic number (C 60 ) m −Au n clusters were discovered recently 21 when C 60 molecules and Au atoms are allowed to interact on a Au(111) substrate. These clusters have a Au core in the shape of a regular two-dimensional Au island and a shell of C 60 molecules with only certain combinations of m and n allowed.…”
mentioning
confidence: 99%